Measurement report: In-depth characterization of ship emissions during operations in a Mediterranean port - L. Le Berre; L. Le Berre; L. Le Berre; B. Temime-Roussel; G. M. Lanzafame; B. D'Anna; N. Marchand; S. Sauvage; S. Sauvage; M. Dufresne; L. Tinel; T. Leonardis; et al. (Atmospheric Chemistry and Physics)
A summertime field campaign was conducted in Marseille, one of the major cruise and ferry ports in the Mediterranean, to provide comprehensive analysis of in-port ship emissions. High-temporal-resolution data were simultaneously collected from two monitoring stations deployed in the port area to examine the composition in both the gas and the particulate phases. More than 350 individual plumes were captured from a variety of ships and operational phases. Gaseous emissions are predominantly composed of NOx (86 %) and CO (12 %), with SO2 and CH4 each accounting for about 1 %. Although non-methane volatile organic compounds (NMVOCs) make up less than 0.1 % of the gaseous phase, they can be as high as 10 % under specific operational conditions. Submicron particles (PM1) are mainly composed of organics (75 %), black carbon (21 %), and sulfate (4 %) that is not balanced with ammonium. Among the ship-related characteristics investigated, the operational phase is the most influential, with a 3-fold increase in submicron particle (PM1) emissions, along with higher relative contributions of black carbon (BC) and sulfate and the detection of vanadium, nickel, and iron during manoeuvring/navigation compared to at berth. Pollutant levels in the port are higher than those found at the urban background site, with average concentrations of NOx, PM1, and particle numbers up to twice as high in the port. Analysis of the maximum concentrations reveals that pollutants such as SO2 and trace metals, including vanadium and nickel, are 2 to 10 times higher in the port area. This study provides robust support for enhancing source apportionment and emission inventories, both of which are crucial for assessing air, health, and climate impacts of shipping.